THE RELATIONSHIP BETWEEN ORGANIZATIONAL CULTURE AND COMPETENCE WITH ORGANIZATIONAL COMMITMENT IN EMPLOYEES OF BUMD BINJAI, NORTH SUMATRA - Komariyah, Imas; Prayudi, Ahmad; Edison, Emron; Laelawati, Kania (Jurnal Riset Bisnis dan Manajemen, 2023)
This study aimed to examine the influence of organizational culture and competence on organizational commitment in BUMD Binjai. The purpose of this study was to determine, assess, and analyze the partial and simultaneous influence of organizational culture and competence on organizational commitment. This study used a quantitative method with data collection techniques through distributing questionnaires to 124 respondents using random sampling technique. Data analysis was carried out using descriptive and verification analysis. The results of the study descriptively showed that organizational culture was considered strong to very strong, competence was considered good to very good, and organizational commitment was considered good to very good. Meanwhile, the results of the study verifiably showed that organizational culture had a positive and significant influence on organizational commitment, competence had a positive and significant influence on organizational commitment, and organizational culture and competence simultaneously had a positive and significant influence on organizational commitment.